Representasi Gender dalam Novel-Novel Bertema Islam Karya Pengarang Perempuan Muslim Indonesia: Analisis Postfeminisme - Prasojo, Albertus; Susanto, Dwi (Humanis, 2025)
Literary works reflect the author's thoughts and the socio-cultural context of their time. This study aims to examine the representation of women and postfeminism in two Islamic-themed novels: Perempuan Berkalung Sorban by Abidah El Khalieqy and Ketika Mas Gagah Pergi by Helvy Tianna Rosa. Using a qualitative method and postfeminist theory, the study analyzes how women are portrayed and how postfeminist values emerge. The findings reveal that in Perempuan Berkalung Sorban , women are depicted within the confines of a conservative Islamic boarding school life. In Ketika Mas Gagah Pergi , women are constrained by stereotypes of the ideal woman. Both novels illustrate postfeminist ideas through the female characters’ freedom to choose their own paths, highlighting autonomy and identity within an Islamic cultural context.